Factors of a social nature associated with prematurity risk in a city in Sao Paulo - Cruz, Aline Adryane Morishigue Bassiga da [UNESP]; Santos, Lucas Cardoso dos [UNESP]; Oliveira Minharro, Michelle Cristine de; Romanholi, Renata Maria Zanardo [UNESP]; Prearo, Alice Yamashita [UNESP]; Alencar, Rubia Aguiar [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2023)
Objective: To identify the associations of factors of a social nature with prematurity.Methos: This is a cross-sectional study with a correlational method, carried out from a database of a medium-sized municipality in the countryside of Sao Paulo, containing information on all newborns from January 2018 to July 2020, aimed at the identification of social and biological risks after birth.Results: The analysis included 4,480 newborns, of which 78.9% were classified as usual-risk babies and 21.1% as at-risk babies. Among the risk factors of a social nature for newborns analyzed in the present study, there was a higher prevalence of newborns whose head of household had no income, had mothers under 16 years of age, a dead sibling aged less than 5 years and mothers who did not undergo prenatal care, with the last two having association with prematurity.Conclusion: Factors of a social nature were associated with prematurity. This study made it possible to improve the newborn surveillance database, facilitating the elaboration and planning of health care.
Keywords: Primary health care; Infant; newborn; Risk factors; premature; Social vulnerability